Childhood and School: time and spaces of children - Anabela Rute Kohlmann Ferrarini; Fabiana Rodrigues Oliveira Queiroz; Raquel Gonçalves Salgado (Universidade Federal do Rio Grande do Sul, 2016)
Childhood is analysed, in this article, as an axis to discuss the chronological time, delimited by a linearity ordered by progress and rationality. Combining Mario Quintana's poetic writings with the dialogues and the experiential maps produced by children, the aim of this text is to discuss how time and spaces reverberate in childhood construction and children educational processes, in order to question the calculate and predictable dimensions assumed by these categories in this social context. Therefore, we search to give visibility to the unexpected time in children experiences, in school, by highlighting how, in this space, they operate breaks in the continuous, progressive and linear temporality.